Penerapan Manajemen Risiko Berbasis ISO 31000 pada Usaha Dagang Perkakas: Studi Kasus UD Anugrah Perkakas - Rahma Khairunnisa Amalia; Ghina Aulia Asy-syifa; Maisya Hayina Zahra; Nilam Meylani (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
MSMEs are a crucial pillar of the Indonesian economy, facing various risk management challenges, particularly in tool trading businesses like UD Anugrah Perkakas in Taraju Village, Kuningan. This study aims to analyze the implementation of ISO 31000-based risk management to identify, analyze, evaluate, and control risks that could potentially disrupt business operations and sustainability. The research method used is descriptive qualitative with observation, in-depth interviews, and documentation studies. The identification results revealed 28 risks classified into six categories: market, marketing, finance, operations, human resources, and legal. The risk evaluation revealed one high risk, namely raw material price instability, and the majority of risks were in the medium and low categories. The implementation of ISO 31000 provides a comprehensive overview of weaknesses and mitigation priorities, thereby improving the continuity and resilience of UD Anugrah Perkakas' operations.